2005
DOI: 10.3138/jvme.32.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Technology: Its Effects on Small Group “Problem-Based Learning” Interactions in a Professional Veterinary Medical Program

Abstract: The objective of this investigation was to ascertain whether and how the introduction of a new technology (WebCT) influenced faculty teaching styles while facilitating small group problem-based learning (PBL) sessions in a professional veterinary medical (PVM) program. The following questions guided the study: (1) How does the use of technology affect faculty teaching behaviors? (2) Do the facilitators' interactions with WebCT technology change over the course of one semester? (3) What is the perceived impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Qualitative studies of educational technologies in PBL have focused on how the innovations have impacted the PBL process. These include the incorporation of visual triggers for problem scenarios (Barron, Lambert, Conlon, & Harrington, 2008); mobile devices (Chan et al, 2015); online social networks (Rowe, 2012); online searching (Jin, Bridges, Botelho, & Chan, 2015); a Learning Management System (LMS;Schoenfeld-Tacher, Bright, McConnell, Marley, & Kogan, 2005); online guides (Ryan, Dolling, & Barnet, 2004); and a purpose-designed online environment (Valaitis, Sword, Jones, & Hodges, 2005). There was a general agreement that educational technologies were useful learning tools in PBL to enhance learning and teaching (Barron et al, 2008), facilitate reflective reasoning in clinical contexts (Rowe, 2012), increase flexibility for learning, and to enhance students' ability to deeply process content (Valaitis et al, 2005).…”
Section: Educational Technologiesmentioning
confidence: 99%
“…Qualitative studies of educational technologies in PBL have focused on how the innovations have impacted the PBL process. These include the incorporation of visual triggers for problem scenarios (Barron, Lambert, Conlon, & Harrington, 2008); mobile devices (Chan et al, 2015); online social networks (Rowe, 2012); online searching (Jin, Bridges, Botelho, & Chan, 2015); a Learning Management System (LMS;Schoenfeld-Tacher, Bright, McConnell, Marley, & Kogan, 2005); online guides (Ryan, Dolling, & Barnet, 2004); and a purpose-designed online environment (Valaitis, Sword, Jones, & Hodges, 2005). There was a general agreement that educational technologies were useful learning tools in PBL to enhance learning and teaching (Barron et al, 2008), facilitate reflective reasoning in clinical contexts (Rowe, 2012), increase flexibility for learning, and to enhance students' ability to deeply process content (Valaitis et al, 2005).…”
Section: Educational Technologiesmentioning
confidence: 99%
“…They suggest that unknowingly, teachers will automatically teach according to their own learning style, which may be incongruent with the students' learning preferences. This is reinforced by the study by Schoenfeld-Tacher et al (2005) who observed teachers vary their teaching styles according to their own learning styles. Antepohl and Herzig's (1999) study of medical students found that the majority of students preferred PBL as it suited their learning styles.…”
Section: Learning Stylesmentioning
confidence: 78%
“…4 The facilitators and students became more familiar with technology and facilitators interacted in a more approachable and caring manner with the students. In…”
Section: Online Learning Groups Are Not Very Common In Southmentioning
confidence: 99%